2017
DOI: 10.7150/ijms.16974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Comorbidities among Hypertensive Patients in China

Abstract: Hypertension is a severe threat to human being's health due to its association with many comorbidities. Many research works have explored hypertension's prevalence and treatment. However, few considered impact of patient's socioeconomic status and geographical disparities. We intended to fulfill that research gap by analyzing the association of the prevalence of hypertension and three important comorbidities with various socioeconomic and geographical factors. We also investigated the prevalence of those comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…These high prevalence figures raise concerns of comorbidity, in which individuals suffer from more than one of the risk factors at a time, with this thought to be highly predictive of end point diseases, disability and death 12. There is evidence of comorbidity risk for factors including obesity, DM and HTN, predominantly coming from industrialised countries13–15 and LMICs16–18; however, evidence on NCDs comorbidity scants in Bangladesh. This is important as the patterning of NCDs is not uniform across countries of different income classification, with a higher prevalence of some NCDs risk factors, such as DM, found in higher socioeconomic groups in many studies in LMICs, contradicting those from higher income countries 19…”
Section: Introductionmentioning
confidence: 99%
“…These high prevalence figures raise concerns of comorbidity, in which individuals suffer from more than one of the risk factors at a time, with this thought to be highly predictive of end point diseases, disability and death 12. There is evidence of comorbidity risk for factors including obesity, DM and HTN, predominantly coming from industrialised countries13–15 and LMICs16–18; however, evidence on NCDs comorbidity scants in Bangladesh. This is important as the patterning of NCDs is not uniform across countries of different income classification, with a higher prevalence of some NCDs risk factors, such as DM, found in higher socioeconomic groups in many studies in LMICs, contradicting those from higher income countries 19…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 , 19 ] There was a low incidence of SAEs and a low rate of discontinuations due to TEAEs. The most frequent TEAE (hyperlipidemia) is often comorbid with hypertension, [ 32 ] and the most frequent treatment-related TEAE (dizziness) is a common adverse reaction with ARBs. [ 33 ] There were no clinically meaningful trends in any treatment group with respect to laboratory parameters, including high-density lipoprotein cholesterol, total cholesterol, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the population was generally old with an average age of 70 years old, one of independent risk factors for the comorbidities, especially for stroke. On the other hand, recent study indicated that different comorbidities of hypertension influenced the patients' choices of hospital class to visit in China, that the patients with coronary heart disease were more likely to visit higher-classed hospitals instead of community hospitals [26]. There are also some limitations in this study.…”
Section: Resultsmentioning
confidence: 83%